The Role of Angiogenesis Factor in Bladder Tumors - Sanaa Jawed (University of Thi-Qar Journal of Science, 2019)
The study designed to detect Ang-1 expression as angiogenesis factor in bladder tumor tissues, and to clarifythe relationship between Ang-1 and clinicopathological grade of bladder cancer. In this study, the expression of Ang-1 in tumor cells was investigated in (30) patients with transitional cell carcinoma of bladder (TCC) and (20 )patients with inflammatory lesions of the bladder (BIL) as acontrol group from the histopathology laboratories ofAl-Hussain Teaching Hospital and private laboratories in Thi-Qar Province,Iraq . The tissue sections wereanalyzed immunohistochemically (IHC) to detection of Ang-1. The results showed a high positiveimmunohistochemical Ang-1 expression of TCC tissues than in BT tissues (76.7 % versus 40%; p≤ 0.01).Furthermore, the significantly highest level of Ang-1 positive cells was detected in the groups with the highestclinical grade (p≤ 0.05). Ang-1 antigen expression could be indicator of aggressive behavior of bladder cancer